The Effect Of Human Resource Training And Development On Employee Performance In The Lahat Regency Environmental Service - Wendi Agustian; Melia Handayani; Saparudin Saparudin (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study was to determine the effect of training and human resource development on employee performance at the Lahat Regency Environmental Service.The results of the study showed that (1) training had a significant partial effect on performance, as evidenced by the calculated t value > t-table (5.205 > 2.005). (2) human resource development had a significant partial effect on performance, as evidenced by the calculated t value > t-table (2.177 > 2.005). (3) Human Resource Training and Development has a significant simultaneous effect on Employee Performance at the Lahat Regency Environmental Service. This can be seen from the calculated f value > f table (59.997 > 2.005) and the significance value is smaller than the significance level (a) of 0.05 (0.000 < 0.05).